Cultural Heritage Tourism and Sustainable Tourism Development Strategy in Morotai Island District - Susilawati Ibrahim (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the opportunities for developing cultural heritage tourism based on sustainable tourism models in Pulau Morotai District. Methodology: This study used a qualitative descriptive method. Data were collected through field research, interviews with government stakeholders in Pulau Morotai, and documentation from relevant reports, books, journals, and articles. Data analysis applied qualitative techniques to examine sustainable tourism indicators based on the WCAD framework. Main Findings: Pulau Morotai has significant potential to develop sustainable cultural heritage tourism due to its historical legacy, such as World War II sites and cultural landmarks. However, challenges include the limited involvement of local communities and NGOs, and overdependence on government and foreign investors. Improvement in stakeholder participation, infrastructure, and promotion strategies are needed to realize this potential. Novelty/Originality of this study: This study contributes original insights into how a remote district like Pulau Morotai can utilize its cultural heritage as a strategic asset for sustainable tourism development. It highlights specific sustainability indicators and local governance dynamics that are rarely addressed in existing literature on Indonesian tourism planning.